Health Information System and Their Impact on The Quality of Healthcare at Benghazi Medical Center - Randa Gadalla; Mahmoud Ahmed (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objectives. The quality of health care delivery or the effectiveness of health planning and policy making depend on the availability of accurate and timely information to support decision-making. Broadly, Hospital Information System (HIS) is any form of structured repository of data, information, or knowledge that can be used to support health care delivery or to promote health development. The aim of this study was to examine the role of hospital information systems in improvement of health care outcomes for patients at Benghazi Medical Center. Methods: A questionnaire-based study was conducted in Benghazi Medical center over the period from March to June 2019. Data were descriptively analyzed and presented as counts and percentages. Results: Regarding the improvement of health outcomes, 31.7 % of the responded not agree that the electronic health information system helps to improve the follow-up of patients' health outcomes. Conclusions: There is need for increases the awareness about the benefits of information system, and develop a database to collect factors affecting the HIS failures. There is also need for implementing such application for enhancing communication between all health care providers.